International performance curve
The variables of snow conditions and terrain in cross country ski races make the establishment of time standards for different age groups (such as occurs in track and swimming) impossible to determine. To overcome this problem and to provide athletes with a fairly objective measure of how their performance relates to their national and international rivals the Canada Points List (which is explained here) was created. This points list is similar to that long used in Alpine and other organizations such as the International Tennis Circuits, to help determine an international ranking system, even though athletes may not be competing in "head-to-head" competition. It uses a points formula that is applied to each CCC sanctioned or high level international race to generate points for each individual athlete at that event. It is a method of helping the athlete and coach assess how the athlete may be progressing towards their performance goals.